The Misuse of 1 Malaysia Book Voucher among Undergraduates: A Case Study in Universiti Sains Malaysia - Lim , Chee Ann; Jang, Jata (School of Social Sciences, 2015)
This study discusses the misuse of 1 Malaysia Book Voucher (BB1M) among undergraduates in Universiti Sains Malaysia. The theoretical framework explains the empirical specification of this study. The Logit regression model was used and conducted in this study to estimate the likelihood of misusing the book voucher among undergraduates. The results indicated several methods on misusing BB1M. Among the methods used by undergraduates with regards to misusing the book voucher include exchange BB1M into cash, purchase goods other than books, purchase goods using BB1M for the purpose of resale, exchange BB1M to bookstore vouchers and transfer BB1M to other parties. Additionally, this research also investigates how respondents maximize their utility level by using the BB1M and hence the result of misusing BB1M can be identified from the respondents’ responses. The findings of this study showed the variables women, young people and those who use all the BB1M are significant.